SERANGGA HERBIVORA YANG BERASOSIASI PADA TANAMAN JAGUNG DENGAN JENIS PUPUK BERBEDA - Dewi Hastuti (Jurnal Agroekoteknologi, 2012)
This research aims to determine the indirect influence of fertilizers on the population and diversity of herbivorous insects in sweet corn varieties super sweet. The research was conducted from the month from May to September 2011 in the Pakel , Gelam village, Kelurahan Cipocok Jaya, Kota Serang. Experiments used designed randomized block design (RBD). The data were analyzed by Anova and DMRT 5%. The herbivour diversity analized by Shannon diversity index. Experimental variable is the type of fertilizer, compost siam weed at a dose of 45 tons / ha, with a dose of manure 45 t / ha, and synthetic fertilizer consisting of urea at a dose of 400 kg / ha, SP36 and KCl dose of 150kg/ha dose 150kg / ha and the control of maize without fertilizer. The fourth variable is repeated 6 times. Observations were made every 2 weeks for orders, families and populations of plant-feeding insects (herbivores) by directly counting the insects which at that time was on the plant. The results showed that the type of fertilizer is not directly influenced by the high population of herbivorous insects. Plants are fertilized siam weed compost herbivore species diversity is high, but their population is foreign-low type. While NPK fertilized plants herbivoranya low diversity and population of each type of the highest good in sucking and biting insects pencucuk chewers. Associated herbivorous insects on corn consists of groups biter chewers like grasshoppers (Acrididae) and pencucuk like ticks sucking aphids (Aphididae).Keywords: fertilizer, herbivores, compost, corn, Acrididae, Aphididae